2023
DOI: 10.1186/s12888-023-04808-7
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of non-suicidal self-injury behavior in adolescents with depression: latent class analysis

Abstract: Background Non-suicidal self-injury (NSSI) by adolescent patients with depression has become a serious public health problem. This cross-sectional study aims to identify subgroups of adolescents based on NSSI and explore the factors related to these subgroups. Methods The study recruited 326 in- and out-patient adolescents (263 girls and 63 boys) aged 12 to 18 years (mean = 14.7, SD = 1.6) who had self-injured in the past year. Latent class indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…However, an important gap remains in our understanding of how these two factors might interactively influence NSSI behaviours. Although studies 15 , 16 have documented the individual contributions of alexithymia and peer victimisation to NSSI, few have delved into their combined effects. Adolescents with high alexithymic traits who also experience peer victimisation might be at elevated risk for NSSI as they navigate the compound challenges of emotional dysregulation and social adversity.…”
mentioning
confidence: 99%
“…However, an important gap remains in our understanding of how these two factors might interactively influence NSSI behaviours. Although studies 15 , 16 have documented the individual contributions of alexithymia and peer victimisation to NSSI, few have delved into their combined effects. Adolescents with high alexithymic traits who also experience peer victimisation might be at elevated risk for NSSI as they navigate the compound challenges of emotional dysregulation and social adversity.…”
mentioning
confidence: 99%
“…These individuals perceived that their bodies were out of control when compared to adolescents who did not engage in NSSI. It is widely acknowledged that NSSI often takes place in the early to middle stages of adolescence ( He et al, 2023 ). Adolescence is the period when the body is believed to become more significant in one’s self-concept ( Markey, 2010 ),which helps to understand why NSSI manifests itself primarily during this developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment, including language deficits, memory loss, and attention difficulties, is a central symptom of depression that persists throughout the illness and significantly impairs social functioning ( 29 , 30 , 37 ). This study showed that after treatment, the observation group exhibited a significant reduction in false responses and persistent errors on the WCST ( 26 ), along with a notable increase in completed classifications compared to the Sham rTMS group.…”
Section: Discussionmentioning
confidence: 99%